PENGARUH KEGIATAN MATCHING SHAPE TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI RAUDHATUL ATHFAL KHOIRUNNISAK PALEMBANG - Qanitah Nugraha, Firyal; Handayani, Tutut; Bahtiar, Adi; Mardeli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low gross motor development of children aged 5–6 years is one of the problems In the learning process at Raudhatul Athfal Khoirunnisak Palembang. This study, entitled “The Effect of Shape Matching Activities on Gross Motor Development in Children Aged 5–6 Years at Raudhatul Athfal Khoirunnisak Palembang,” aimed to determine whether shape Matching activities influence children’s gross motor development. This study used a Quantitative approach with an experimental research type. The method used was a Pre-Experimental Design with a One Group Pretest-Posttest. The study sample Consisted of 19 children aged 5–6 years. Data collection techniques used tests and Observations using instruments that had been tested for validity and reliability. Data Analysis techniques used normality tests, homogeneity tests, N-Gain tests, and Paired sample t-tests. Based on the results of the data analysis after the pretest and Posttest, an increase in children’s gross motor skills was observed. The t-test results Showed that the calculated t-value was greater than the t-table (calculated t-value >T-table), thus H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that Shape matching activities significantly influence the gross motor development of 5–6 year-old children at Raudhatul Athfal Khoirunnisak Palembang.